Disorders of acid-base balance and water electrolyte metabolism - Melnikova, O. V.; Ivanenko, T. V.; Grekova, T. A.; Kadzharyan, Y. V.; Danukalo, M. V.; Isachenko, M. I.; Мельнікова, Ольга Валеріївна; Іваненко, Тарас Васильович; Грекова, Тетяна Анатоліївна; Каджарян, Єлизавета Віталіївна; Данукало, Максим Вікторович; Ісаченко, Марія Ігорівна (Запорізький державний медичний університет, 2019)
Disorders of acid-base balance and water electrolyte metabolism Part 1 General Pathophysiology. Subsection 3 Typical disorders of metabolism: Manual for independent work for the students of the 3rd course of international faculty speciality “General medicine” English medium of instruction.